PENGARUH EFEKTIVITAS PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT), MIND MAPPING, DAN TALKING CHIPS TERHADAP PENINGKATAN KEMAMPUAN BERPIKIR KRITIS SISWA (Studi Eksperimen pada Siswa Kelas VIII Mata Pelajaran IPS di SMPN 1 Jalaksana Kabupaten Kuningan) - Misbahul Khoer (Equilibrium: Jurnal Penelitian Pendidikan dan Ekonomi, 2019)
Abstract: This study aims to determine students critical thinking skills after applying the cooperative learning model Numbered Head Together (NHT), Mind Maping and Talking Chips. The method used is the experimental method with Counterbalanced Design research design. The instrument in this study used multiple choice questions. The population of this study was all eighth grade students of Junior High School 1 Jalaksana. The sample used is class VIII A, class VIII B and class VIII C where each class consists of 38 students and in the research process will be given different treatments for each class. Data collection techniques were obtained through tests of critical thinking skills and data analysis techniques carried out included normality tests, homogeneity tests, and t-test. The results show that there are differences in students' critical thinking skills from each treatment carried out in each class with different methods and different topics so that the proposed hypothesis can be accepted. Viewed from the results of the average value of critical thinking abilities of students in each study that the NHT method is always higher than the Talking Chips method, and the Talking Chips method is always higher than the Mind Maping method, so it can be concluded that the Numbered Head type cooperative learning model Together (NHT) is more effective in improving students'critical thinking skills.Keywords : Critical Thinking Ability, Demand Curve, Numbered Head Together (NHT), Mind Mapping, Offers, Requests, Talking Chips